2002
DOI: 10.1192/apt.8.5.342
|View full text |Cite
|
Sign up to set email alerts
|

Simulated patients and objective structured clinical examinations: review of their use in medical education

Abstract: Simulated or standardised patients have been used in medical education and other medical settings for some 30 years (Box 1). Their use encompasses undergraduate and postgraduate learning, the monitoring of doctors' performance and standardisation of clinical examinations. Simulation has been used for instruction in industry and the military for much longer (Jason et al, 1971) but the first known effective use of simulated patients was by Barrows & Abrahamson (1964), who used them to appraise students' perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 17 publications
1
50
0
6
Order By: Relevance
“…Furthermore, questions can be tailored to the level of skill to be assessed, and the patient variable in examination is uniform across participants. 29 As many studies have reported, this kind of investigation, including overt observation, could have caused some pharmacists to feel uncomfortable, which may have resulted in deviations from their regular behavior. On the other hand, some of the participants' performance may have more accurately reflected their performance in daily practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, questions can be tailored to the level of skill to be assessed, and the patient variable in examination is uniform across participants. 29 As many studies have reported, this kind of investigation, including overt observation, could have caused some pharmacists to feel uncomfortable, which may have resulted in deviations from their regular behavior. On the other hand, some of the participants' performance may have more accurately reflected their performance in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 As greater emphasis is placed on demonstrating individual competency, pharmacist documentation will continue to serve a key role. Although this may appear to be a relatively easy task, experience is required to know what information to include and how to communicate it in a manner appropriate for the patient medication record.…”
Section: Discussionmentioning
confidence: 99%
“…There also are some advantages related to the use of virtual cases, including control and safety, feedback from the assessor (simulators), questions can be tailored to level of skill to be assessed, the patient scenario is uniform across participants. 29 Because the data were collected during a 3-month period, pharmacists who participated early in the assessment may have passed on information to those who had not participated yet and this may have influenced their performance. Nevertheless, because the researcher assessed each pharmacist's performance based on unique, real-life patient situations that were not predictable, and posed questions to the pharmacist related to those situations, possible sharing of information among the participants was not considered a serious limitation.…”
Section: Discussionmentioning
confidence: 99%
“…It might be tempting to use volunteers or other nonprofessionals to play the patients in the OSCE stations, because of the limited availability of (or expense of hiring) professionals. It would be equally easy to underestimate the demands of training them to portray the clinical situation accurately and respond in a realistic butcrucially -consistent fashion to the varying approaches of the candidates (Wallace et al, 2002). In our view, the benefits of using experienced professionals who have had training in simulating mental illness and the experience of playing patients in OSCEs with the reliability and consistency required are inestimable.…”
Section: Role Playersmentioning
confidence: 95%